Personal Pronouns in Balinese and English With Reference To Tiga Satua Bali - Sintha Satwika, I Gusti Ayu Agung; Artawa, Ketut; Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): March 2016, 2016)
This research is aimed at investigating and analyzing the meaning and application of personal pronouns in Balinese and English. The data of this writing were collected from a bilingual book entitled Tiga Satua Bali . This study was conducted using the qualitative method of which the discussion was presented descriptively. The data of this study were collected using observation technique and were analyzed using the qualitative method and comparative technique. The result of this study indicates that the personal pronouns can be classified into three, namely first, second, and third personal pronouns which  can be found in Basa Singgih, Andap, and Kasar. This classification was made based on the context of situation and speech participants
Keywords: personal pronouns, participant, context of situation